Plutarch and Dio on Cicero at the trial of Milo - Fotheringham, Lynn S. (Oxford University Press, 2014)
The accounts of the trial of Milo given by Plutarch and Dio provide a valuable insight into the working methods of the two writers. A close examination of the incident in relation to the structure of Plutarch’s Life of Cicero confirms that the Life is a carefully structured unit which assumes audience knowledge of events and presents a particular picture of Cicero. A similar exploration of Dio’s account of the failing years of the Republic reveals the historian both playing with annalistic structure and emphasizing this incident in order to highlight the contemporary political breakdown; he too is interested in constructing a picture of Cicero in relation to his context, and hostility to the orator cannot explain all his choices. Granting literary skill and purpose to both of these writers allows us greater insight into the imperial reception of Cicero.